Diversidad de Coniopterygidae y Hemerobiidae (Neuroptera) en el municipio de Nanacamilpa de Mariano Arista, Tlaxcala - Márquez López, Yesenia (Universidad Autónoma Metropolitana, 2017)
The neuropterans are depredatory insects as larval stage as adult, they are considered natural biological controllers. In Mexico are reported 349 species, at present in the state of Tlaxcala only there are two species. A faunistic study and analysis of diversity of the species of Coniopterygidae and Hemerobiidae of the municipality of Nanacamilpa, Tlaxcala, was performed. Specimens were collected systematically with Malaise traps, nets and light traps through 13 months of sampling at two localities of the municipality: Ejido Los Búfalos and Piedra Canteada. The first locality had a pine-oak vegetation at an altitude of 2,884 masl, while the second one had an oak-pine vegetation at 2,850 masl. At both sites three Malaise traps were placed, which alcohol was changed monthly, also sampling with entomological nets took place. Sampling started on September 25 of 2015 and finished on March 3 of 2017. Neuropterans were identified to species level, with a total of 20 species recorded, of which 12 are new records for the state and four are new records for the country, also three morphospecies (one Coniopterygidae and two Hemerobiidae) were recorded and one previously registered at the state. Seasonality of coniopterygids and hemerobiids showed three abundance peaks throughout the sampling period, one at the end of the dry season and two during rainy season. Results of true alpha diversity (order 0) show that with 15 observed species, it would still be expected to find four more species in Los Búfalos and one more in Piedra Canteada, similar results to those obtained through the species accumulation curves. Degree of similarity of the two localities was 0.66 because they share 13 of the 16 species recorded. Forest of Nanacamilpa has a moderate diversity of both families, which could increase if the sampling effort is intensified.; Los neurópteros son insectos depredadores tanto en estado larval como adulto, son considerados controladores biológicos naturales. En México se reportan 349 especies, actualmente en el estado de Tlaxcala únicamente se tiene registro de dos especies. Se realizó un estudio faunístico y análisis de diversidad de las especies de Coniopterygidae y Hemerobiidae (Neuroptera) recolectadas en el Municipio de Nanacamilpa, Tlaxcala. Los ejemplares fueron recolectados sistemáticamente con trampas Malaise y red entomológica durante 13 meses de muestreo en dos localidades del municipio, Ejido Los Búfalos y Piedra Canteada. La primera presenta vegetación pino-encino y está a una altitud de 2,884 msnm y la segunda presenta una vegetación de encino-pino a 2,850 msnm. En ambas se colocaron tres trampas Malaise, a las que mensualmente se les cambió el alcohol, ademásse realizó muestreo con red entomológica en cada salida. Los muestreos mensuales se iniciaron el 25 de septiembre del 2015 y concluyeron el 3 de marzo de 2017. Los neurópteros se determinaron a nivel específico, registrando un total de 20, de las cuales 12 son nuevos registros para el estado y cuatro para el país, además se encontraron tres morfoespecies (una de Coniopterygidae y dos de Hemerobiidae) y una previamente registrada en el estado. La estacionalidad de los coniopterígidos y hemeróbidos reflejó tres picos de abundancia a lo largo del muestreo, uno al final de la época de secas y dos en época de lluvias. Los resultados de la diversidad alfa verdadera (orden 0) muestran que con 15 especies observadas aún se esperarían encontrar cuatro especies en Los Búfalos y una más en Piedra Canteada, resultados similares a los obtenidos en las curvas de acumulación de especies. La similitud entre sitios fue de 0.66 dado que comparten 13 de las 18 especies recolectadas. Los bosques de Nanacamilpa presentan diversidad moderada de ambas familias, la cual podría incrementar si se intensifica el esfuerzo de muestreo